2019
DOI: 10.1002/lary.27952
|View full text |Cite
|
Sign up to set email alerts
|

Chronic laryngitis caused by Mycobacterium Kansasii in a traveler

Abstract: Chronic laryngitis commonly presents with dysphonia, and infectious causes include tuberculosis and endemic mycoses. We present a 58-year-old female with laryngitis for 5 years, fevers, chills, fatigue, malaise, myalgias, anterior neck pain, and night sweats after multicontinent exposure. Bronchoscopy cultures were negative. Bilateral microflap excision of vocal fold lesions demonstrated thickened epithelium and a deep vocal fold mass. Biopsy showed necrotizing granulomatous inflammation with acid-fast bacilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
(21 reference statements)
0
8
0
2
Order By: Relevance
“…5,8 Laryngeal NTM involvement is rare with only 7 prior studies reporting cases. [2][3][4][5][6][7][8] The limited mention of any tracheal involvement in NTM disease comes from one study describing tracheobronchial lesions found on bronchoscopy. 10 Our case demonstrates possible complications, such as subglottic stenosis, from treatment of NTM infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,8 Laryngeal NTM involvement is rare with only 7 prior studies reporting cases. [2][3][4][5][6][7][8] The limited mention of any tracheal involvement in NTM disease comes from one study describing tracheobronchial lesions found on bronchoscopy. 10 Our case demonstrates possible complications, such as subglottic stenosis, from treatment of NTM infection.…”
Section: Discussionmentioning
confidence: 99%
“…Following successful diagnosis and treatment of laryngeal NTM, most of the literature describes complete resolution of disease without complications. [2][3][4][6][7][8] This was not the case for our patient with laryngeal and cervical tracheal NTM disease. Although she initially improved, she developed subglottic stenosis that required dilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found only seven documented cases of laryngeal NTM in the literature [11][12][13][14][15] including the slow-growing Mycobacterium avium, kansasii and malmoense. Presentations included vocal fold mucosal thickening, 11,12,15 multifocal ulcerations 14 and pseudotumor development. 13 To our knowledge, the present case is the first described laryngeal infection by a fast-growing NTM, Mycobacterium fortuitum.…”
Section: Discussionmentioning
confidence: 99%